Impact of chlorhexidine and povidone-iodine antiseptic solutions on the cervicovaginal microenvironment during laparoscopic hysterectomies: a pilot study - Paweł Łaniewski; Gabriella Smith; Phoebe Crossley; Leslie V. Farland; Nichole D. Mahnert; Melissa M. Herbst-Kralovetz (npj Women's Health)
Abstract The use of chlorhexidine gluconate (CHG) as surgical preparation solution has been advocated due to reduced bacterial loads compared with povidone-iodine (PI). We aimed to investigate changes to the vaginal microenvironment among patients who had laparoscopic hysterectomy and were surgically prepped using 4% CHG compared to 7.5% PI. Premenopausal women who underwent laparoscopic hysterectomy for benign conditions and were prepped with either CHG or PI per surgeon’s choice were enrolled. Vaginal swabs and cervicovaginal lavages were collected prior to vaginal preparation and at 4–6 week post-operative visits for microbiome (α and β diversity, bacterial relative abundances, vaginal pH) and immune marker analyses (protein profiles and concentrations). Antimicrobial activity of clinical CHG and PI formulations were tested in vitro using minimal inhibitory and bactericidal concentration assays. Between February 2021 and June 2022, 41 patients were enrolled. Seven patients either withdrew consent or met exclusion criteria for vaginal bleeding. Thirty-four patients had pre-operative samples collected; 13 patients were lost to follow-up. A total of 21 patients with longitudinal samples of pre- and post-operative collection contributed to this study: 13 in the CHG group and 8 in the PI group. Prior to surgery, 75–77% of women in both groups exhibited Lactobacillus dominance. PI did not change overall vaginal microbiome profiles; however, CHG impacted Lactobacillus iners-dominant profiles, shifting to other lactobacilli (50%) or dysbiotic anaerobes (33%). Lactobacillus crispatus-dominant profiles, which are optimal for vaginal health, were not impacted by either antiseptic solution. In vitro assays further confirmed higher susceptibility of L. iners to CHG solution compared to other vaginal lactobacilli species. Pro-inflammatory cytokines or chemokines were not increased in the CHG or PI group. Our study suggests that CHG does not increase the rate of post-operative vaginal dysbiosis, or genital inflammation compared to PI. Species-specific effects of CHG on vaginal lactobacilli and its clinical impact require further investigation.